Pengaruh Media Leaflet Terhadap Pengetahuan Pasien Dalam Meminum Obat Diabetes Tipe 2 Di RS Aisyiyah Pariaman - Muhammad Aldo; Fatridha Yansen (Jurnal Medisains Kesehatan, 2026)
Health education is an effective method to improve patient knowledge, especially in the management of chronic diseases such as type 2 diabetes mellitus. One commonly used educational medium is the leaflet, as it is practical, easy to understand, and can be taken home by patients. This study aims to determine the effect of leaflet media on increasing patient knowledge regarding the proper intake of type 2 diabetes medication at Aisyiyah Hospital in Pariaman. The research results showed a significant increase in patients' knowledge after being given the intervention. Before using the leaflet media, the majority of participatnts scores were in the of 50% to 75% correct answers. Meanwhile, after using the leaflet, the majorit of participants moved to the 87.5 % to 100 % correct answer range. Thus, it can be stated that there was an increase in patient’ knowledge about taking type 2 diabetes medication from the pre-test to the post-test . Based on the results of the Wilcoxon Signed Rank Test, the significance value was 0.000, which is less than 0.05 (p < 0.05). Thus, the leaflet media proved to be effective in improving patient knowledge using a pre-test and post-test approach regarding the correct way to take type 2 diabetes medication. The leaflet also effectively enhanced patients’ understanding of the importance of taking medication regularly, the correct dosage, and proper timing. This increased knowledge is crucial in supporting patient adherence to treatment and preventing further complications. The use of printed media such as leaflets is recommended as part of routine educational interventions in healthcare facilities. Education through leaflets provides information that patients can reread, reinforcing their understanding of the disease and the therapy they are undergoing. Leaflet media supports the sensory process by providing visual information that enhances patient comprehension. Therefore, the use of leaflets in educating type 2 diabetes patients greatly contributes to improving their knowledge regarding proper medication consumption.